2017
DOI: 10.1021/acschembio.6b00994
|View full text |Cite
|
Sign up to set email alerts
|

Development of Autologous C5 Vaccine Nanoparticles to Reduce Intravascular Hemolysis in Vivo

Abstract: The complement system is emerging as a new target for treating many diseases. For example, Eculizumab, a humanized monoclonal antibody against complement component 5 (C5), has been approved for paroxysmal nocturnal hemoglobinuria (PNH) in which patient erythrocytes are lysed by complement. In this study, we developed vaccines to elicit autologous anti-C5 antibody production in mice for complement inhibition. Immunization of mice with a conservative C5 xenoprotein raised high titers of IgGs against the xenogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Nanoparticle-based drug delivery approach has gained pace in recent years for both small molecules such as natural products as well as biomolecules such as peptides [112,114]. Nanoparticles can improve the effectiveness of natural compounds in disease treatment and prevention by increasing their bioavailability, including passing the BBB.…”
Section: Natural Product-based Amyloid Inhibitorsmentioning
confidence: 99%
“…Nanoparticle-based drug delivery approach has gained pace in recent years for both small molecules such as natural products as well as biomolecules such as peptides [112,114]. Nanoparticles can improve the effectiveness of natural compounds in disease treatment and prevention by increasing their bioavailability, including passing the BBB.…”
Section: Natural Product-based Amyloid Inhibitorsmentioning
confidence: 99%
“…A peptide epitope (PADRE peptide) in the C5 vaccine is used to create a recombinant virus-like particles (VLPs). It showed a reduction in hemolytic activity and protect the mice from complement-mediated intravascular hemolysis [60]. Based on the study's result, it is showed that the recombinant VLPs could be used as an alternative or supplement for Eculizumab.…”
Section: Virus-like Particlementioning
confidence: 93%
“…Virus-like particles (VLPs) is one of the alternative types of nanoparticles delivery system [59]. A recent research has shown that the development of autologous C5 vaccine in nanoparticle form is able to elicit strong humoral responses [60]. A peptide epitope (PADRE peptide) in the C5 vaccine is used to create a recombinant virus-like particles (VLPs).…”
Section: Virus-like Particlementioning
confidence: 99%
“…GOx is ∼160 kDa in size, consists of two dimers, two flavin adenine dinucleotide (FAD) and iron cofactors, and is heavily glycosylated, representing more complex multimeric and/or cofactor dependent proteins (Bankar et al, 2009). Lastly, the virus-like particle Qβ is a 30 nm multimeric protein assembly that has been extensively researched as a drug delivery, imaging, and immunotherapy platform (Pokorski et al, 2011; Spohn et al, 2008; Zhang et al, 2017). Our previous study utilized unmilled Qβ/PLGA HME formulations to serve as single-administration vaccine devices in vivo .…”
Section: Introductionmentioning
confidence: 99%